PENGARUH MEDIA PEMBELAJARAN DIGITAL TERHADAP HASIL BELAJAR DI SMP NEGERI 1 PATTALASSANG KABUPATEN GOWA - Nurwasila, Najwa; Bunyamin, Andi; Mustamin; Syahid, Akhmad; Hasan, Salim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of digital media on student learning outcomes in Islamic Religious Education subjects at SMP Negeri 1 Pattallassang, Gowa Regency. This study uses a quantitative approach with an ex post facto research type. The study population was 281 students in grades VII, VIII, and IX, while the sample was 74 students determined using a simple random sampling technique with the Slovin formula. Data collection techniques were carried out through observation, questionnaires, and documentation. The research instrument was a Likert scale questionnaire to measure the use of digital media, while learning outcome data were obtained from documentation of students' daily test scores. Data were analyzed using descriptive statistical analysis, normality tests, linearity tests, simple linear regression analysis, and hypothesis testing (t-test) with the help of IBM SPSS Statistics version 29. The results showed that the use of digital media did not significantly affect student learning outcomes in Islamic Religious Education subjects. This is evidenced by the results of the t-test which obtained a significance value of 0.155 (> 0.05), so that the alternative hypothesis (Ha) was rejected and the null hypothesis (H₀) was accepted. The regression coefficient of 0.197 indicates a positive relationship between digital media and learning outcomes, but this relationship is not statistically significant. This finding suggests that digital media use is not yet a primary factor influencing student learning outcomes. Learning outcomes are thought to be more influenced by other factors, such as learning motivation, learning interests, student abilities, teacher-implemented learning strategies, and a supportive learning environment. Therefore, the use of digital media needs to be integrated with innovative and interactive learning strategies to provide a more optimal contribution to improving student learning outcomes.